2020
DOI: 10.1002/ccr3.3485
|View full text |Cite
|
Sign up to set email alerts
|

Management of life‐threatening acute respiratory syndrome and severe pneumonia secondary to COVID‐19 in pregnancy: A case report and literature review

Abstract: The novel coronavirus disease 2019 (COVID-19) has been declared as a "pandemic outbreak" and public health emergency of utmost international concern. 1 With over 37 million confirmed cases and 1 million deaths (as of 12/10/2020), the pandemic continues to harm significant number of people worldwide. Approximately, 5% of the infected cases are

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 40 publications
0
17
0
1
Order By: Relevance
“…At that point, 13 articles were assessed for eligibility [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. After reading the full texts, one article was removed: Chong et al [ 15 ] reported the case of a 41-year-old woman, 32 weeks pregnant, who developed severe acute respiratory distress syndrome (ARDS) from SARS-CoV-2 infection, necessitating emergency Cesarean section in the intensive care room.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…At that point, 13 articles were assessed for eligibility [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. After reading the full texts, one article was removed: Chong et al [ 15 ] reported the case of a 41-year-old woman, 32 weeks pregnant, who developed severe acute respiratory distress syndrome (ARDS) from SARS-CoV-2 infection, necessitating emergency Cesarean section in the intensive care room.…”
Section: Resultsmentioning
confidence: 99%
“…At the end of the assessment phase, 12 records were included in this review; all were case reports involving a total of 12 pregnancies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Table 1 presents the characteristics of the studies included in the final review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations